Analisa Kepuasan Siswa: Peran Kualitas Pelayanan Sekolah - Erna Dwiastuti; Dwiyadi Surya Wardana (Jurnal Ilmiah Aset, 2018)
The aim of this research is to know the influence of dimensions of service quality schools namely tangibles, reliability, responsiveness, assurance, and empathy against student satisfaction (study on class X SMK Negeri Pontianak) 1. This research was conducted at SMK Negeri 1 the Pontianak and take grade X as respondents. The population of this research that is 449 students with a total sample of 67 students. Data collected through questionnaire and analyzed with multiple regression method. The results showed that only tangibles and assurance that influence significantly to student satisfaction. Thus, SMK Negeri 1 can improve the tangibles (physical evidence) aspect of the schools such as equipment, school supplies, and the added convenience of classes and can improve the assurance (assurance) student perceived as increase the ability of teachers and student employees in the trial.